One-step fabrication of highly stable, durable, adhesion enhanced, flexible, transparent conducting films based on silver nanowires and neutralized PEDOT:PSS. Issue 7 (22nd March 2023) - Devaraju, Subramani; Mohanty, Aruna Kumar; Won, Du-hyun; Paik, Hyun-jong
Abstract : The developed flexible hybrid AgNWs/N-PEDOT:PSS TCFs displayed low sheet resistance, high transmittance, low haze, good adhesion, and mechanical stability. Abstract : Silver nanowires (AgNWs) are one of the best material substitutes for indium tin oxide (ITO) in next-generation flexible, foldable, and bendable transparent conducting electrodes (TCEs) due to their very low sheet resistance, good transparency, higher flexibility, and ease of processing. However, they still suffer from some drawbacks such as larger surface roughness, poor stability, high haze, and poor adhesion to substrates. In this work, we report the fabrication of flexible and bendable TCEs with good mechanical stability and optical and electrical properties from the hybrid of AgNWs and neutralized PEDOT:PSS by simple one-step roll-to-roll coating. Imidazole was employed to neutralize the commercial grade PEDOT:PSS for minimal loss of conductivity. Hydroxypropyl methylcellulose (HPMC) was used to improve the hybrid dispersion and as a binder to enhance the adhesion with the substrate. Polysiloxane was used as the overcoating protective layer on the AgNWs/N-PEDOT:PSS TCF to enhance stability against oxidation and corrosion. The AgNW hybrid TCF showed a sheet resistance of 20 Ω sq −1 and optical transmittance over 95% with a low haze value of ∼1. The AgNW hybrid TCFs displayed better adhesion and exceptional mechanical stability with almost no difference in sheet resistance after 5000 repeated bending cycles. This method of hybrid TCF fabrication offering exceptional stability, low sheet resistance, good transparency and lower haze holds great potential in the context of highly flexible electronic applications.